An Infrequent Presentation of Open Traumatic Dislocation of Second to Fifth Metatarsophalangeal Joints - Tathagath Tiwary; Rajavel Kalirajan; Gowthaman Natarajan (Journal of Orthopedics and Joint Surgery)
Post-traumatic dislocation of multiple adjoining lesser toes is an infrequent presentation. The regional anatomy of the metatarsophalangeal (MTP) joints is such that various structures, primarily the soft tissues such as plantar plate and ligaments, provide hindrance to the closed reduction of the joint. Here, we present a case of open dorsal dislocation of the second to fifth MTP joints in the right foot following a road traffic accident (RTA). The patient came to the emergency room (ER) with a history of RTA resulting in injury to the right foot. On examination, the plantar aspect of the foot had an open wound with protrusion of the underlying bones, giving a “marble ball appearance.” There was an increase in interdigital web space on presentation along with discordance of articulation of MTP joints. All findings were confirmed on radiographs. Multiple closed reduction attempts were made but all were futile. Hence, open relocation was done through the dorsal and plantar approaches by extending the open wound and making three incisions—one dorsally and two on the plantar. Excision of the plantar plate and the joint capsule was done along with K-wire fixation.